Preparation of biomass-based hydrogels and their efficient heavy metal removal from aqueous solution - Zhang, Mingyue; Zhou, Yaru; Wang, Fangling; Chen, Zeshao; Zhao, Xu; Duan, Weidong; Yin, Guangting; Yang, Xinling; Li, Junfeng; Yin, Quanyu; Zhao, Mingqin (Frontiers in Chemistry, 2022)
In this work, a porous tobacco straw-based polyacrylic acid hydrogel STS-PAA with high adsorption performance was prepared by polymerizing pretreated waste tobacco straw (TS) with acrylic acid/potassium acrylate by UV radiation initiation. The adsorption performance of metal ions was investigated. The effects of different temperatures, adsorption times, pH values and initial concentrations of metal ions on the adsorption amount of heavy metal ions were investigated. The results showed that the hydrogel had a high removal rate of Pb2+, Cd2+ and Hg2+ in aqueous solution. The adsorption of Pb2+ was particularly effective, with the adsorption amount reaching 1.49 mmol g-1. The surface of the hydrogel was rough with abundant and uniform pore structure. The adsorption mechanism of metal ions was investigated by XPS. The chemical structure and morphology of the hydrogels were characterized by FT-IR, EDS, SEM and XPS.